Rozwiąż nierówność
a ) 4(x-3)² - (2x-5)² ≥2
b) 9(2/3x-2)² <(1-2x)²
c) -0(2-x)² -(1-3x)(3x+1) ≤ 11
d) (1/4+2)² + 1/4( 1/2x)(1+1/2x) ≥ 0
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a) 4(x-3)² - (2x-5)² ≥2²
4(x²-2*x*3+3²) - (2x²-2*2x*5+5²) ≥4
4(x²-6x+9) - (4x²-20x+25) ≥ 4
4x²-24x+36-4x²-20x+25 ≥4
-24x-20x ≥ 4-25-36
-44x ≥ -65/ : (-44)
x ≥ 65/44= 1 i 1/11
chyba tak:)
a) 4(x-3)² - (2x-5)² ≥2²
4(x²-2*x*3+3²) - (2x²-2*2x*5+5²) ≥4
4(x²-6x+9) - (4x²-20x+25) ≥ 4
4x²-24x+36-4x²-20x+25 ≥4
-24x-20x ≥ 4-25-36
-44x ≥ -65/ : (-44)
x ≥ 65/44= 1 i 1/11